Hydatidosis prevalence and risk factors in Peru's Ninacac-pasco district population 2001 - Núñez, Eloísa (2003)
Objetive: To determine the prevalence and risk factors of hydatidosis in a Peruvian town general population. Design: Transversal analytic study. Material and methods: In 412 residents from the urban area and 261 from the rural area a blood sample was obtained for serology and a survey was applied; hydatidosis cases were those positive to Elisa and Western Blot tests. Results: Hydatidosis prevalence was 9,8% in the rural area and 8,2% in the urban area. Significant risk factors were: age from 11 to 40 year-old, cattle breeder occupation, and residual water discharge within the house (rural area); and a protection factor was dog feeding with cooked viscera. Conclusions: Hydatidosis risk factors in a Peruvian district were economically productive population, direct labor with livestock and dog feeding with viscerae. Implementing a program of local harm control and extending it to the country’s highlands is suggested.